Building a Fortress of Faith in East Indonesia: Islamic Religious Education for Muallaf Family in Abun Tribe, Tambrauw, Southwest Papua - Nur, Indria; Rizal, Samsul; Sukman, Sukman; Abdillah, Fardan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2024)
Building synergy between local culture and education is a strategic effort to create communities and families that have a strong identity, and are able to adapt to global dynamics. This article aims to analyze the implementation of Islamic education in the muallaf family of the Abun Tribe in Baun Village, Tambrauw, Southwest Papua who are a minority in their environment and tribe. The existence of inner conflicts, marginalized in social life, causing personal problems, even poverty, is a serious problem in the hearts of these seekers of God. This research uses a qualitative method with a phenomenological approach. Data were obtained through observations and interviews with informants from muallaf families. The results showed that the practice of religious education in the muallaf family of the Abun Tribe is still weak, so it really needs continuous guidance from various parties. Islamic education coaching based on local culture and tradition is one of the alternative choices to realize the ideal Islamic family, sakīnah, mawaddah wa raḥmah in the Abun muallaf family